In vivo inhibition of epileptiform afterdischarges in rat hippocampus by light‐activated chloride channel, stGtACR2. (8th December 2022) - Acharya, Anirudh R.; Larsen, Lars Emil; Delbeke, Jean; Wadman, Wytse J.; Vonck, Kristl; Meurs, Alfred; Boon, Paul; Raedt, Robrecht
Abstract: Aims: The blue light‐sensitive chloride‐conducting opsin, stGtACR2, provides potent optogenetic silencing of neurons. The present study investigated whether activation of stGtACR2 in granule cells of the dentate gyrus (DG) inhibits epileptic afterdischarges in a rat model. Methods: Rats were bilaterally injected with 0.9 μl of AAV2/7‐CaMKIIα‐stGtACR2‐fusionred in the DG. Three weeks later, afterdischarges were recorded from the DG by placing an optrode at the injection site and a stimulation electrode in the perforant path (PP). Afterdischarges were evoked every 10 min by unilateral electrical stimulation of the PP (20 Hz, 10 s). During every other afterdischarge, the DG was illuminated for 5 or 30 s, first ipsilaterally and then bilaterally to the PP stimulation. The line length metric of the afterdischarges was compared between illumination conditions. Results: Ipsilateral stGtACR2 activation during afterdischarges decreased the local field potential line length only during illumination and specifically at the illuminated site but did not reduce afterdischarge duration. Bilateral illumination did not terminate the afterdischarges. Conclusion: Optogenetic inhibition of excitatory neurons using the blue‐light sensitive chloride channel stGtACR2 reduced the amplitude of electrically induced afterdischarges in the DG at the site of illumination, but this local inhibitory effect was insufficient to reduce the duration of the afterdischarge. Abstract : Electrical stimulation of the perforant path in the rat model causes afterdischarges to appear bilaterally (yellow arrows) in hippocampal‐parahippocampal structures (black box) (EC—Entorhinal cortex; DG—Dentate Gyrus; CA1‐CA3—Hippocampus proper). Activation of optogenetic chloride channel (stGtACR2) in DG (blue box) was expected to reduce afterdischarge propagation (blue arrow and gray box). Activation of stGtACR2 was observed to reduce amplitude of afterdischarge activity only at the illuminated site (blue box) without affecting afterdischarge occurring at contralateral hemisphere